0028 Engaging stakeholders to maximise dissemination and use of injury data documents. (26th April 2015) - Dao, Dan
Abstract : Statement of purpose: Public health practitioners routinely develop and publish data documents to inform public health programming. Although much time and staff resources are used to prepare such documents, rarely do we assess how these documents are being disseminated and used. In light of this information gap, the Kansas Injury Prevention Program (KIPP) engaged coalition stakeholders to learn how they used a previously developed large data report on childhood injuries. The goal was to find out how the document was used and identify stakeholders' additional data needs to inform the creation of an updated data report. Methods/Approach: KIPP conducted key informant interviews with 5 coalition stakeholders. Interview questions asked about knowledge and use of a 2012 childhood injury document, including what sections of the documents were used and not used. Respondents were also asked about how they used the data and what type of data they would like to see in future documents. Results: There were varying levels of report use among respondents. Some used the data every day and some did not know the report existed. The report was organised by database, rather than injury topic area, to facilitate report development and data interpretation, but partners reported this made it harder to use. Stakeholders also reported rarely using rates and confidence intervals, but commonly used percentages and counts. Stakeholders reported using the data to make their case to community leaders, regardless of statistical considerations. Conclusions: Interview results showed that partners used data for their advocacy needs and didn't specifically focus on interpreting numbers correctly. Understanding what data are needed and how data are actually being used can help KIPP maximise use of data documents and facilitate correct interpretation of injury data. Significance and contribution to the field: Creating documents of value is challenging. As time and resources become increasingly scarce, it is necessary to pursue projects which will have defined and measurable impact. This extends beyond programming into creating and disseminating data reports. Engaging stakeholders and providing technical assistance for data interpretation is an important step in ensuring dissemination and maximising use of injury data documents.